Inversion of Electron Tomography Images Using $L^2$-Gradient Flows — Computational Methods (Journal of Computational Mathematics, 2018)
In this paper, we present a stable, reliable and robust method for reconstructing a threedimensional density function from a set of two dimensional electric tomographic images.By minimizing an energy functional consisting of a fidelity term and a regularization term,an $L^2$-gradient flow is derived. The flow is integrated by a finite element method in thespatial direction and an explicit Euler scheme in temporal direction. The experimentalresults show that the proposed method is efficient and effective.
Keywords: Computational Inversion; Reconstruction; Electric Tomography.